Usage of mandala art therapy toward social interaction skills of children with autism spectrum disorder / Kim Tae Hoo - Kim , Tae Hoo (2018)
Individuals with Autism Spectrum Disorder (ASD) have impairments in language developments and social interactions; they are not able to relate well to people, they have trouble expressing their emotions and sustaining conversations. These tendencies make it difficult for parents and caregivers to understand the emotional state of children with ASD. This case study investigates the advantage of mandala art therapy in helping parents and caregivers recognize the emotional state of children with ASD without pressuring them to verbalize their feelings. Mandala art therapy is known widely in the study of art therapy as an approach that provides a safe environment for clients to explore their inner self. It was introduced by Carl Gustav Jung as a way to express feelings in the field of psychology. The data obtained in this case study were collected within twelve weeks, for one session per week. Subjective and objective methods of data collection were implemented. The subjective analysis employs Jungian psychotherapist Susanne F. Fincher's interpretation of colours in a mandala. It also includes an in-depth analysis describing the behavioural changes of the two participants throughout the twelve-week mandala art therapy sessions. For the objective analysis, Autism-Spectrum Quotient (AQ) questionnaire was used before and after the intervention to determine whether there is an improvement in their social interaction skills after going through twelve sessions of mandala art therapy. After twelve weeks of observation, it is concluded that mandala art therapy would be beneficial for parents and caregivers as an intervention tool that explores the emotional conditions of children with ASD.